PENGUATAN KOMPETENSI PUBLIC SPEAKING BERBASIS SIMULASI UNTUK MENINGKATKAN KESIAPAN KARIR MAHASISWA - Dewirahmadanirwati Dewirahmadanirwati; Ridha Hasnul Ulya; Ineng Naini; Amrullah Amrullah; Afrida Afrida; Asmawati Asmawati (PUAN INDONESIA, 2026)
Speaking skills are crucial for students to face academic and professional demands in the global era; however, low self-confidence and difficulties in delivering ideas systematically remain prevalent. This community service activity aims to enhance students' communication competence through the "Speak with Confidence" training program. Involving 50 students, the program was implemented using an andragogical approach and experiential learning, comprising needs assessment, interactive material delivery, simulations, role-play, and comprehensive evaluation using pre-tests, post-tests, performance observation, and satisfaction surveys. The results indicated significant improvements in both knowledge and skills. Conceptual understanding increased by 26.25%, while practical speaking skills improved by 27.16%, with the most notable increase in self-confidence (35%). Furthermore, participant satisfaction reached 92.4%. These findings demonstrate that a practice-oriented andragogical approach effectively reduces psychological barriers and builds students' communication competence, strategically preparing adaptable and competitive graduates for the professional world.